حماية الطفل اليتيم واللقيط بين الفقه والقانون - ميمي العيد - رحابي عمار (جامعة المسيلة, 2021)
الطفولة مرحلة عمريـة يتعلـق بسنه الذي يعتبر مرحلة حساسة و خطيرة و سنــه يختلـف من دولة إلى أخرى و الطفل اليتيــم واللقيط هو أخطـر طفـل عرضة للمخاطر و للمجتمـــــع ، لذلك أولته الشريعة الإسلامية اهتماما فائقا و حثت على رعايته و حذرت من تجاوز حقــــــــوقه فذكـــــــــره الله عــــــــز و جل أربع و عشرين مرة في اثنتي عشر سورة اشتملت على ثالثة و عشرين أية، و مــن خلال التمعـن في الآيات نجد أن اللـــــه عز و جل أعطى اهتماما واسعا للطفـــــــل. و نهى على قهر اليتيم واللقيط و حــــــث على الاهتمام به باعتباره فاقـد لمعيلـــه و لوالديه أو أحدهما فيكون بحاجة إلى الرعاية . نجد أن الاتفاقيات الدوليــــــــة و التشريعـــــات العربية أخذت من الشريعة الإسلامية حقوق الطفل اليتيم واللقيط و كرستها في بنود و مـــــــواد عملـت على حماية الطفل ببقائه حـــــــيا و تجريم قتله و نصت على حضانة اليتيـــــــــم واللقيط و توفيـــــــر له الأسرة و العائلة البديلة التي تعوضه عن أسرته الحقيقة التي فقدهــا فهي واجــــــب على الأسر، و إن لم توجـد فالدولة تتكفل به و ذلك بوضعه في ديار و مؤسسات و جمعيات تكفل باليتيم واللقيط و في حالة ما قرر تسليم الطفل للحاضن و إمتنع عن تسليمه يتعرض للعقوبة المقررة قانونا ،حضانة الطفل اليتيم واللقيط بحاجة إلى نفقة تشمل الغذاء و العلاج و الكسوة و السكن إذا إمتنــــــع القائم بها يتعـــرض للعقوبة كما أن تـرك الطفل اليتيم واللقيط و إهماله و تعريضه للخطر و المــــــــــرض يتعاقب قانونا لأن القانون نص على حماية اجتماعية تمثلت في هيئة وطنية للطفولة و مصالح الوســط المفتوح تعمـل على حماية الطفل المعرض للخطر كالاستغلال الجنسي حماية الطفل مدنيا وجزائيا و منع تعريضهما للخطر كما نـص على حمايــة الطفل اليتيــــم واللقيط بتمكينهما و إجبارهما على التعليم فهو حق مكفولا دستوريا و جعل التعليـم مجانا أي بدفع مبلغ رمزي فالدولة تكفل ذلك بمنحهما منحــــــــة مدرسيــــة إلى جانـب الأدوات المدرسية و يقـف إلى جانبهما رجــال سخرهم الله عز و جل لخدمة اليتامى واللقطاء بتوفيـــر لهم اللباس و الأدوات المدرسية . إلى جانب الصحة و التعليم فقد حظـر تشغيل الأطفال فكل من يعارض ذلـك يتعرض لعقوبة حماية الطفل اليتيم واللقيط قضاءا . الكلمات المفتاحية: اليتيم - اللقيط – الطفل– الحماية الجزائية- الحماية المدنية. Abstract: Childhood is an age stage related to its age, which is considered a sensitive and dangerous stage, and its age varies from one country to another. The orphan and foundling child is the most dangerous child exposed to dangers and to society. Therefore, Islamic Sharia gave him great attention and urged his care and warned against violating his rights, so God Almighty and Majestic reminded him Twenty-four times in twelve surahs that contain twenty-three verses, and by examining the verses, we find that God, the Mighty and Sublime, gave extensive attention to the child. And he forbade subjugating the orphan and foundling and urged attention to him as he has lost his breadwinner, his parents, or one of them, so he needs care. We find that international conventions and Arab legislation have taken from Islamic Sharia the rights of the orphan child and enshrined them in articles and articles that worked to protect the child by keeping him alive and criminalizing his killing. Families, and if not, the state takes care of him by placing him in homes, institutions and associations that take care of the orphan and foundling. In the event that he decides to hand the child to the custodian and refuses to hand him over, he is subject to the legally prescribed penalty. The custody of the orphan and foundling child needs an expense that includes food and treatment And clothing and housing, if the person in charge refrains from it, shall be subject to punishment, as well as leaving the orphan and foundling child, neglecting and exposing him to danger, and the disease is punishable by law because the law stipulates social protection represented by a National Commission for Childhood and the interests of an open environment work to protect the child at risk such as sexual exploitation and child protection It also stipulates the protection of the orphan and foundling child by empowering them and forcing them to learn, as it is a right guaranteed by constitution. He made education free, i.e. by paying a symbolic amount. The state guarantees this by granting them a school grant along with school supplies, and men who have been subjugated by God Almighty to serve orphans and foundlings by providing them with clothes and school supplies stand by their side. In addition to health and education, child labor is prohibited. Anyone who opposes this is subject to the judicial punishment of protecting the orphan and foundling child. Key words: orphan - foundling - child - criminal protection - civil protection.
Keywords: اليتيم - اللقيط – الطفل– الحماية الجزائية- الحماية المدنية.